Reading habits, interests and needs of rural folk towards providing library services in the social laboratory area in Pila, Laguna - Lantican, Editha S. (1985)
A study was conducted in three barrios in Pila, Laguna covered by the UPLB-SEARCA barrio development project to determine the livelihood pattern, literacy level, educational status, reading habits of the people and the materials available, informational sources used, subject matter preference and their reaction to the idea of putting up a library in the area. A 23-item interview questionnaire was used with 196 respondents, consisting of 57 household heads or husbands, 72 housewives, and 67 school-aged youth. The households were chosen at random and each was represented by a family membership of three--the husband, wife and a school-aged son or daughter. The predominant means of livelihood were farming (42 percent) and fishing (10 percent), with the rest distributed in non-agricultural vocations such as jeepney and tricycle driving.